Co-existence of maternal overweight/obesity, child undernutrition, and anaemia among mother-child pairs in Ethiopia. - Biniyam Sahiledengle; Lillian Mwanri; Pammla Petrucka; Hiwot Tadesse; Kingsley Emwinyore Agho (Public Library of Science (PLoS), 2024)
Ethiopia is currently known to be the most food-insecure country in sub-Saharan Africa, where childhood undernutrition remains endemic. While attention is increasingly being paid to childhood undernutrition in Ethiopia, a current surge of "triple burden of malnutrition" (TBM) has received less attention. The purpose of this study was to determine the prevalence of TBM and identify the associated factors in Ethiopia. Data were from the Ethiopian Demographic and Health Surveys (2005-2016) and a total of 20,994 mother-child pairs were examined in this study. The TBM was our primary outcome variable, which encompasses three types of nutritional problems-when a mother may be overweight/obese, while her child is stunted, wasted, or underweight plus has anaemia under the same roof. A multilevel logistic regression explored the individual- and community-level factors associated with TBM. Our study indicated that children under-five years of age were anaemic, stunted, wasted, and underweight [49.3% (95% CI: 48.7-49.9), 43.1% (95% CI: 42.4-43.7), 10.3% (95% CI: 9.9-10.7), and 27.6% (95% CI: 27.0-28.1)] respectively. The overall prevalence of TBM was 2.6% (95% CI: 2.39-2.83). Multilevel analyses revealed that TBM was more likely to occur among children aged 12-23 months (AOR: 2.54, 95% CI: 1.68-3.83), 24-35 months (AOR: 1.54, 95% CI: 1.03-2.29), children perceived by their mothers to be smaller than normal at birth (AOR: 1.94, 95% CI: 1.48-2.56), who experienced fever in the past 2 weeks (AOR: 1.58, 95% CI: 1.24-2.01), and lived in urban settings (AOR: 1.79, 95% CI: 1.13-2.86). Lower odds of TBM were reported among female children (AOR: 0.59, 95% CI: 0.47-0.72), and those who lived in rich households (AOR: 0.69: 95% CI: 0.49-0.98). TBM was found to be present in almost three percent of households in Ethiopia. Addressing the TBM through double-duty actions will be of critical importance in achieving malnutrition in all its forms in Ethiopia.